(untitled) (Bioagro, 2018)
The study of the linear relations between plant characteristics is important to identify traits for indirect selection of plants with large fresh and dry matter production. The objectives of this research were to evaluate the linear relations among traits of jack bean (Canavalia ensiformis) and identify traits for indirect selection. In experimental area of 160 m2, 194 plants were collected randomly at 202 days after sowing. The traits plant height, stem diameter, number of nodes, number of leaves, number of pods, fresh matter of pods, fresh matter of aerial part without pods, fresh matter of aerial part, dry matter of pods, dry matter of aerial part without pods and dry matter of aerial part were measured in each plant. The mean and coefficient of variation were calculated for each trait. The linear relations among the traits were studied through correlation and path analyzes. The number of pods showed to have positive linear relation with fresh and dry matter of pods. The number of leaves has positive linear relation with fresh and dry matter of aerial part without pods and with fresh and dry matter of aerial part. It is concluded that the number of pods and leaves can be used for indirect selection of jack bean plants.